Targeted cyber attacks : multi-staged attacks driven by exploits and malware - Sood, Aditya K.; Enbody, Richard J. (Waltham, MA : Syngress, 2014)
Cyber-crime increasingly impacts both the online and offline world, and targeted attacks play a significant role in disrupting services in both. Targeted attacks are those that are aimed at a particular individual, group, or type of site or service. Unlike worms and viruses that usually attack indiscriminately, targeted attacks involve intelligence-gathering and planning to a degree that drastically changes its profile. Individuals, corporations, and even governments are facing new threats from targeted attacks. Targeted Cyber Attacks examines real-world examples of dir.
8 Challenges and Countermeasures8.1 Real-Time Challenges; 8.1.1 Persisting False Sense of Security; 8.1.2 Myths About Malware Infections and Protection; 8.2 Countermeasures and Future Developments; 8.2.1 Building a Strong Response Plan; 8.2.2 End System Security; 8.2.3 User Centric Security; 8.2.4 Network Level Security; 8.2.5 Security Assessment and Patch Management; 8.2.6 Next-generation Defenses; References; 9 Conclusion; References; Abbreviations.
Online resource; title from title page (Safari, viewed May 6, 2014).
Includes bibliographical references.
Keywords: Computer networks -- Security measures; Cyberspace -- Security measures; Computer crimes -- Prevention; Réseaux d'ordinateurs -- Sécurité -- Mesures; Cyberspace -- Security measures; Computer crimes -- Prevention; Computer networks -- Security measures; Internetkriminalität; Malware